Stripes the tiger - Leroy, Jean, 1975-; Delaporte, Bérengère, 1979- (Peter Pauper Press, Inc., 2016)
Stripes is a small tabby cat who dreams of being a ferocious tiger, but when his owner takes him to the zoo he meets a real tiger who wants to switch places with him.